2014
DOI: 10.1186/1471-2458-14-626
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia among under-5 children in the Ghanaian population: estimates from the Ghana demographic and health survey

Abstract: BackgroundAnemia in children continues to be a major public health challenge in most developing countries, particularly in Africa. Anemia in the early stages of life leads to severe negative consequences on the cognitive as well as the growth and development of children, which may persist even after treatment. We examine the prevalence of anemia in under-five children in the Ghanaian population to help inform and serve as a guide to health policies and possible interventions.MethodsData from the 2008 Ghana Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
91
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 15 publications
25
91
10
1
Order By: Relevance
“…The prevalence of anaemia among children aged 6-23 was 56.7% as compared to 42.3% in children aged 24-59 months (p=0.027). Similar findings were reported earlier, where the prevalence of anaemiaamong children under 2 years was 85.1% and 74 8% among children 2-5 years of age (p<0.001) [2].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The prevalence of anaemia among children aged 6-23 was 56.7% as compared to 42.3% in children aged 24-59 months (p=0.027). Similar findings were reported earlier, where the prevalence of anaemiaamong children under 2 years was 85.1% and 74 8% among children 2-5 years of age (p<0.001) [2].…”
Section: Discussionsupporting
confidence: 80%
“…The results of the current study revealed that the prevalence of anaemia (Hb<11.0g/dl) in children under five in rural areas in Hohoe municipality was 48.1% with mean Hb (10.8±1.70).This finding is lower compared to the overall prevalence of anaemiareportedearlier in the rural areas of Ghana, 74% [2,11].This improvement could be due to the high LLIN ownership and usage, high coverage of antenatal care clinics attendance by pregnant women, high SP-IPTp and iron supplements uptake during pregnancy, which has resulted in good iron stores in both the mother and child. It could also be due to the clearance of parasitaemia in the blood through prompt treatment with effective antimalarial drugs.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Around 66 patients were diagnosed to be normocytic normochromic anaemia in which 30 patients were males followed by 36 patients were females which was not in favour to the results seen in the study done by BhasinAet al in which62 patients out of 100 patients had normocytic anaemia and 30 patients out of 100 patients had microcytic anemia. [13] Microcytic anaemia was more seen in 41-50 age group (31 patients), Normocytic…”
Section: Types Of Anaemiamentioning
confidence: 99%